Gayface - Kolodner, Ash 1987-; Peirce, Kimberly 1967-; Roth, Jordan; RuPaul 1960- (Lucia/Marquand, 2023)
From 2011 to 2015, Brooklyn-based photographer Ash Kolodner (born 1987) traveled across the United States photographing hundreds of LGBTQIA+ individuals of all ages. They made two consecutive portraits of each of their subjects, photographing them twice during the same sitting: once with eyes closed and then with eyes open. These diptychs symbolize the vulnerability many have felt at the outset of discovering their personal identities, and then the realization and self-actualization manifest in the intimate and profound process of coming out. Through more than 180 color portraits, along with subject interviews and contributing texts by filmmaker Kimberly Peirce and Tony award-winning producer Jordan Roth, Gayface reflects the beauty, intimacy and sometimes the pain of a community kept in the shadows for decades. Ultimately these pictures and this handsome volume represent a revelatory statement on the profound humanity we all share
Keywords: Kolodner, Ash -- 1987-; Geschichte 2011-2015; Porträtfotografie; LGBT; Bildband